Revitalizing a Healthy Lifestyle for the Elderly: A Community-Based Preventive Effort at Santa Elisabeth Primary Clinicnik Pratama Santa Elisabeth - Deskrisman Stefan Mendrofa; Lia Mayang Sari Sijabat; Angenia Itoniat Zega (CENDEKIA: Jurnal Pengabdian Masyarakat, 2025)
Indonesia’s rising life expectancy has led o a growing elderly population, often facing health issues due to low physical activity and limited knowledge of healthy living.To enhance elderly well-being through a community-based health education and physical activity program at Klinik Pratama Santa Elisabeth Medan.The program involved three phases: preparation (permits, surveys, pre-tests), implementation (health screening, NCD education, elderly exercise), and evaluation (post-tests, discussions). Key health indicators were measured. Participants showed improved awareness of healthy lifestyles and physical fitness. Regular exercise enhanced flexibility, strength, and reduced anxiety. Community engagement ensured program continuity. Community-based interventions effectively promote healthy aging and have a broader impact on societal perceptions of elderly health.